Bank deposits of households during Covid-19 in the Visegrad countries - Cichorska, Joanna; Czech, Maria; Puszer, Blandyna (Journal of Finance and Financial Law, 2022)
The purpose of the article/hypothesis: The main objective of the article is to examine the impact of the Covid-19 pandemic on the value of bank deposits of monetary financial institutions (MFIs) in the V4 countries, i.e. the Czech Republic, Poland, Slovakia and Hungary. The specific objective of this study is to investigate the situation in the market of bank deposits in the Visegrad Group countries during the Covid-19 pandemic. In relation to the adopted goals, the hypothesis was formulated that the Covid-19 pandemic determines the amount of money invested by households from bank deposits in the V4 group, but the determinants of this saving and the direction and strength of their impact are varied. Methodology: The achievement of the set objectives was based on theoretical studies and empirical research. In the theoretical studies a critical analysis of source literature was applied. Empirical research involved time series analysis and multiple linear regression analysis. Results of the research: The results of the study allowed for positive verification of the hypothesis, and the study objectives were achieved. It has been shown that changes in the number of Covid-19 cases, as well as changes in the number of deaths and the number of vaccinations performed for Covid-19 in individual V4 countries translate into the propensity or aversion to deposit money in bank financial institutions. This is confirmed primarily by regression analysis, but also by time series analysis.